Reading and Writing Emily Carr - Parkinson, John Edward (My University, 1988)
Emily Carr is a critically neglected figure in Canadian literature. Our current perception of her is defined almost totally by biographies and myth. This thesis attempts to demonstrate the sorts of strategies of truth which permeate the discourses of biography and autobiography. I confront the question of identity by examining how Emily Carr's writing about herself differs from that of her biographers. Where does the self that is allegedly carried by and through language find itself to be? Writing is treated as a representational medium; the page is the canvas painted by the grapheme. While I believe that we cannot avoid defining Carr in traditional terms of family, society, geography etc., I hope that this thesis provides an alternate reading of familiar concepts. I wish to represent Emily Carr as a Western writer but one with a "difference."
Keywords: English Language and Literature; English Language and Literature